2014
DOI: 10.1007/s11064-014-1404-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Src Kinase in the Caspase-1 Pathway After Hypoxia in the Brain of Newborn Piglets

Abstract: Hypoxia induces a cerebral inflammatory response, which contributes to brain injury. Inflammasomes are complex intracellular molecular structures that initiate the inflammatory cascade. Caspase-1 and interleukin 1-β (IL-1β), have been established as markers of inflammasome activation. Src kinase, a cytosolic non-receptor protein tyrosine kinase, is linked to cell proliferation and differentiation and is up regulated during hypoxia. The role of Src kinase in the above pathway is not fully understood. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In lactating sows, feed reduction was demonstrated to reduce levels of expression of NLRP3 , CASP1 , and IL1B in liver approximately two-fold, indicating potential for influences of environment on porcine inflammasomes (Gessner et al, 2015). Hypoxia in piglets leads to brain injury and is associated with caspase-1 activation and small increases (<2-fold) in IL-1β release in the cerebral cortex (Angelis et al, 2014). Additionally, activation of NLRP3 , ASC ( PYCARD ), and IL1B transcription in aortal tissue was observed in a porcine atherosclerosis model (Li et al, 2013); the authors indicate that this may be due to cholesterol crystals.…”
Section: Inflammasome Research In Swinementioning
confidence: 99%
“…In lactating sows, feed reduction was demonstrated to reduce levels of expression of NLRP3 , CASP1 , and IL1B in liver approximately two-fold, indicating potential for influences of environment on porcine inflammasomes (Gessner et al, 2015). Hypoxia in piglets leads to brain injury and is associated with caspase-1 activation and small increases (<2-fold) in IL-1β release in the cerebral cortex (Angelis et al, 2014). Additionally, activation of NLRP3 , ASC ( PYCARD ), and IL1B transcription in aortal tissue was observed in a porcine atherosclerosis model (Li et al, 2013); the authors indicate that this may be due to cholesterol crystals.…”
Section: Inflammasome Research In Swinementioning
confidence: 99%
“…[22] Single protein inhibition with small molecules resulted in satisfactory in vivo results in the HI porcine model. [10,22] In order to ensure adequate energy failure after hypoxia we measured the high energy compounds in the groups and our hypoxic groups were very comparable in the ATP and PCr levels. HT or Src inhibition did not restore the energy failure but they were applied one hour following the hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…[9] We have previously shown that cerebral hypoxia results in increased activity of Src kinase and CaM kinase IV in neuronal nuclei of the cerebral cortex of newborn piglets. [10,11]…”
Section: Introductionmentioning
confidence: 99%
“…During this procedure, piglets that undergo hypoxia, become acidotic, and develop hypotension with mean arterial pressure at the limits of loss of autoregulation. This experimental model of combined brain hypoxia ischemia as well as the details in changes of blood pressure and acid-base status of the ventilated piglets is previously described [13]. …”
Section: Methodsmentioning
confidence: 99%